Rancang Alat Pencacah Rumput Pakan Ternak Tenaga Surya Berbasis Mikrokontroller Dengan Sinar UV Sebagai Penghigienis Rumput - Euaggelion Eko Firman Setiawan Yohanes; Enno Agdelliano Diniardi; Muhammad Syah Radian; Agung Budi Prasetyo; Dinda Azzahra Permata Hati; Risse Entikaria Rachmanita (Indonesian Journal Publisher, 2023)
The innovation of a lawn mower using a microcontroller based solar energy system combined with UV LED light as a microbe minimizer aims to increase the innovation of the lawn mower by using the PLTS system from the use of sunlight that is cleaner and more efficient which replaces fossil fuels from diesel and turns grass into grass. The chopper results are more hygienic for ruminant livestock. The innovation of the lawn mower in this activity is presented in the form of a ready to use machine. The method used in the realization of the concept and design as well as the design of the tool is carried out by going through the literature study stages, designing tool design concepts, designing tool making, and testing tool performance. main frame: height 200cm, width 50cm, length 60cm with a thickness of 4 mm angled iron frame, chopper cover componen 50 cm long and 15cm wide, axle iron components 1,5 inch, the diameter of the chopping knife blade is a 30cm using an AC motor drive. Total electrical energy and tool performance generated by the solar power system on the Smart Machine Grass chopper for 2 hours when the engine is running without charging, the average voltages is 14,62 Volts, current is 2,08 Ampere, and produces an average energy of 6,18 watts and obtained the performance of the tool in chopping grass of 63,4 kg for 2 hours with an average of 2,64 kg every 5 minutes.